1998
DOI: 10.1006/dbio.1997.8816
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Immunolocalization of p59c-fynTyrosine Kinase in Rat Eggs

Abstract: Fertilization overcomes meiotic arrest by triggering a series of biochemical events, resulting in activation of the egg. A small group of protein tyrosine kinases (PTKs) have been identified in eggs of invertebrates and lower vertebrates and inhibitor studies have suggested that they play a role in late events of egg activation. A recent study using the sea urchin system demonstrated that Fyn kinase was expressed in eggs and was activated within minutes of fertilization. In the present study, Western blot anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
44
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 30 publications
17
44
0
Order By: Relevance
“…However, its expression and localization in oocyte is not known. Expression of Fyn, a member of Src kinase family (SFKs), is demonstrated and its activity is detected in rat eggs, which represents the first demonstration of a PTK in mammalian eggs (Talmor et al 1998). Furthermore, other members of SFKs, including Src and Yes, were detected in rat eggs (Talmor-Cohen et al 2004).…”
Section: Discussionsupporting
confidence: 48%
“…However, its expression and localization in oocyte is not known. Expression of Fyn, a member of Src kinase family (SFKs), is demonstrated and its activity is detected in rat eggs, which represents the first demonstration of a PTK in mammalian eggs (Talmor et al 1998). Furthermore, other members of SFKs, including Src and Yes, were detected in rat eggs (Talmor-Cohen et al 2004).…”
Section: Discussionsupporting
confidence: 48%
“…For example, while mammalian eggs express Fyn, Yes, and in some cases, Src (Talmor et al 1998, Talmor-Cohen et al 2004a), the results of two different studies indicate that these kinases are not required for the unique sperm-induced calcium oscillations (Kurokawa et al 2004a, Mehlmann & Jaffe 2005, which trigger egg activation in mammals (Carroll 2001). Instead, these calcium oscillations are triggered directly by a sperm-borne phospholipase that does not require PTK regulation (Cox et al 2002).…”
Section: Introductionmentioning
confidence: 41%
“…2A). In general, the distribution of Fyn in the mouse egg resembled with that previously reported for the rat egg (Talmor et al 1998) except that specific localization of Fyn to the meiotic spindle was not observed in the mouse oocyte under these conditions. After fertilization, Fyn remained concentrated in the egg cortex, including the region of sperm incorporation (Fig.…”
Section: Expression Of Fyn Kinase In the Mouse Oocytementioning
confidence: 48%
“…Rats were killed 14 h after hCG administration. Cumulus-enclosed MI eggs were removed from the oviductal ampullae into Toyoda HEPES (TH; Ben-Yosef et al 1998) medium or into Ca 2C -and Mg 2C -free TH (TH K/K ) medium, both supplemented with 0.4% BSA (fraction V, Sigma; Talmor et al 1998). Cumulus cells were removed by a brief exposure to 400 IU/ml of hyaluronidase (Sigma).…”
Section: Mii-ovulated Eggssupporting
confidence: 44%